Synoptic-Statistical Analysis of Ozone\'s (O3) Extreme Days in Tehran - ali reza karbalaee doree; Sayyed Mohammad Hosseini (تحقیقات کاربردی علوم جغرافیایی)
Air pollution is one of the most important natural hazards in cities that is one of the priorities of climate research.  In this research, synoptic situation of days polluted by ozone in Tehran have been studied and by environmental to circulation approach and cluster analysis. At first, was formed a matrix in 2417*41. Rows are indicated days and columns represent the number of stations. by cluster analysis and Ward method eight different clusters were identified. The results showed that the frequency of the ozone days have a seasonal trend and more can be seen in the first half of year in these cases the establishment subtropical high pressure in Iran. Therefore, cause the persistency of pollution in Tehran.